CALCIFIED STYLOHYOID LIGAMENT: A SUSPECTED CASE OF EAGLE’S SYNDROME (Journal of Forensic Medicine & Toxicology, 2023)
Eagle’s syndrome is a rare condition that is caused by extension of the styloid process or calcification of the stylohyoid ligament, which creates pressure on the different neck and head structures and results in a combination of symptoms including discomfort and a feeling of a foreign body. When this occurs, a person may sometimes die suddenly, which may go unnoticed if a thorough autopsy is not performed. We present a case report of the calcified stylohyoid ligament revealed during the autopsy and address its medicolegal implications.
Keywords: stylohyoid ligament; Eagle’s syndrome; sudden death